8(10m+30)=-3(m+3)

Simple and best practice solution for 8(10m+30)=-3(m+3) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 8(10m+30)=-3(m+3) equation:



8(10m+30)=-3(m+3)
We move all terms to the left:
8(10m+30)-(-3(m+3))=0
We multiply parentheses
80m-(-3(m+3))+240=0
We calculate terms in parentheses: -(-3(m+3)), so:
-3(m+3)
We multiply parentheses
-3m-9
Back to the equation:
-(-3m-9)
We get rid of parentheses
80m+3m+9+240=0
We add all the numbers together, and all the variables
83m+249=0
We move all terms containing m to the left, all other terms to the right
83m=-249
m=-249/83
m=-3

See similar equations:

| -9=-4+b/2 | | 4(5x+9)=-22+38 | | 4.45k+9.2=17.6 | | -25-6n=-42 | | -2h+3=-1 | | 2^x-5=11^3x | | 144+(3x+12)=180 | | 90+21=4x31 | | 3(1p-1)+6=1p-4 | | 1/9(2m-16)=(2m+4) | | 6x-7=19x-13 | | 9.5+10x=-50.5 | | x8x-7x+3.7=0 | | 216=(r/2)+214 | | (27u+18)=5(u+8) | | (y+6)+7(13.3)+4=180 | | x+4(2)=13 | | -3x+18=-21 | | (y+6)+(7×13.3+4)=180 | | 3b+1=-10 | | 3x-8=16+5 | | 1/9(27u+18)=5(u+8) | | 3(4+x)+5=5 | | 30=6x+2x-2 | | a+1.4=25 | | t-0.7=9.78 | | x/0.8=7.6 | | 6v^2=13v-8=-3 | | 71.25r=7.5 | | -(-3x+4)+(4x-2)=-2(x+2) | | 6x-4=120 | | 2(x+4)=81 |

Equations solver categories